Oral Epithelial Cytokines: A Review - Shnawa, Ibrahim Mohamed Saeed (Issues and Development in Health Research Vol. 4, 2021)
Oral mucosal epithelia as other types of mucosal epithelia are known traditionally as protective tissues. In the present chapter, attempts were made to introduce oral epithelia as non-lymphoid, non-myeloid tissue with an immune potentials. Epithelia is the plural of the singular epithelium. They are specialized layers that covered the external surface of the organs forming the body. Today, opinions holds the believe that oral epithelial cells have TLR system and can recognize microbial invaders .Microbial invaders in turn, induce epithelia to produce pro-inflammatory TH1,TH2 cytokines and Chemokines. The induction processes described as species and strain specific. Natural epithelial cytokine production have been assured by a number of an in-vitro models. Oral epithelial cytokine interplayed several immune functions like regulation of local immune responses, mediate autoimmune disease and induce tissue damage in case of increased secretion. They express multi-factorial influences on mucosal immune compartment, be an integral part of the local innate immune responses and might have a future implication in vaccine immunity .